Optimisasi Sistem Manajemen Transaksi Pada Stasiun Pengisian Listrik Berbasis Website - Imamar Fabiddunya, Puteri; Amini, Aisyah; Gumilang Saputra, Ary Eka; Saputra, Zanu; Afriansyah, Riki (Jurnal Inovasi Teknologi Terapan, 2024)
The growth in the use of electric vehicles has become a significant trend in recent years, supported by the establishment of several electric charging stations in urban areas. The reliability of transaction system management at electric charging stations is one of the main focuses. Therefore, research is needed to create a transaction system at a simple electric charging station that utilizes a website-based platform. The aim of this research is to optimize transaction system management at electric charging stations. Based on the results obtained in this research, the tool is capable of charging from an AC source which is converted to DC by a 12V 5A power adapter. Charging is carried out using a 12V 3.5Ah battery with a nominal price option of 5,000 to 25,000. When the top-up reaches the nominal value filled in, the top-up will be cut off by the relay and the transaction receipt will automatically come out. The receipt data that comes out will be stored on the website. Operators and users can monitor transaction data via the STARIK website.